(untitled) (Jurnal Bina Praja, 2019)
The low quality of the Senior Executive Service Officials (SES) of the State Civil Apparatus (Aparatur Sipil Negara/ASN) was due its selection process which was highly political and lack in objectivity, fairness, and transparency. The low quality and competence impeded government activities and made them unable to compete with the private sector. The implementation of the merit system in the selection process of ASN Senior Executive Service (SES) which emphasizes the qualification, competency, performance, as well as fairness and openness, was needed to produce professional Pratama SES. The purpose of this study was to identify and analyze the implementation of the merit system in the selection of SES in the Central Java Provincial Government. The research problem of this study was how the merit system was implemented in the selection process for the SES in the Central Java Provincial Government. The theory utilized in the study was the merit system, on the dimensions of competency, qualification, work performance, and fairness. A qualitative approach was used in this study to describe and analyze the results. The primary data was collected from interviews with the sources, while the secondary data was collected using literature reviews of relevant books, journals, documents, and regulations. The location of the study is the Regional Staffing Unit (Badan Kepegawaian Daerah/BKD) of Central Java Provincial Government. Data analysis was conducted by pattern determination, data reduction, data presentation, and verification/conclusion. The study showed that the merit system in the recruitment process of the Central Java Provincial Government’s Pratama SES was not implemented fully. Some Pratama SES selected using the system were still unable to perform their duties optimally, especially in responding, analyzing, or taking decisions/policy related to their duties. The dimension of the merit system has not yet been fully grasped and carried out, such as qualifications, competencies, and performance assessment.